In utero Head Circumference is Associated with Childhood Allergy - Eviston, David P.; Minasyan, Anna; Mann, Kristy P.; Campbell, Dianne E.; Nanan, Ralph K. (Frontiers in Pediatrics, 2015)
Background Altered fetal growth is known to be associated with allergic disease. Specifically, increased head circumference at birth has been linked to asthma and elevated IgE. However, few studies have examined a link between early fetal anthropometry and allergic disease. The aim of this study was to examine head circumference at mid-gestation in children diagnosed with allergy. Methods This was a retrospective cohort study, comprising pregnancies delivered between 10/2006 and 9/2010 at Nepean Hospital, Australia. Exclusion criteria were illegal drug use, alcohol consumption, gestation <35 weeks and gestational hypertension. Pregnancy data was sourced from the Nepean Obstetric Database. Atopic diseases (asthma, atopic dermatitis and IgE-mediated food allergy) were assessed by questionnaire, at age 1-5 years. Infants from pregnancies with completed questionnaires, who also had a mid-gestation ultrasound scan, were included (N=121). Multiple logistic regression techniques were used to model head circumference against the development of allergies. Results Smaller head circumference at mid-gestation was associated with an increased odds of allergic disease in children aged 1-5 years. A 1 mm smaller head circumference was associated with a 7% increased chance of allergies being later diagnosed, adjusted for gestation (95% CI: 1%-14%, p=0.036). Head circumference at mid-gestation was also inversely correlated with the presence of multiple atopic disease. Conclusions Smaller mid-gestational head circumference is associated with early childhood allergic disease, which suggests fetal programming of allergic disease occurs before mid-gestation. This suggests that mediators such as brain-derived neurotropic factor may be dysregulated early in utero in a milieu, which also predisposes to atopic disease.